Review on indoor air quality in Indianbuildings. Issue 1 (April 2021) - Gopalakrishnan, Preethi; Saravanakumar, P; Joshi, Nikhil N; Harish, B; Jeyanthi, J
Abstract: World Health Organisation reports Chronic Obstructive Pulmonary Disease (COPD) and lung cancer has the second in top ten reasons of death worldwide accounting to 4.7 million deaths in 2016 next to Ischaemic heart disease and stroke. COPD and Lung cancer is a chronic disease which arises while (i) Inhaling a small amount of irritants over a long period of time (ii) Inhaling a large amount of irritants over a short period of time. Therefore Polluted air or contaminated air is the main reason behind the cause of COPD. Air Quality is classified into Ambient Air Quality (AAQ) and Indoor Air Quality (IAQ). IAQ has more influence on people than AAQ since 90% of time person spends indoor such as in home, office, industrial buildings worksite, etc, . Therefore proper maintaining proper indoor quality within the confined building can save people from diseases like COPD. Indoor Air Quality get poorer due to reasons like smoking, incomplete combustion of solid fuel, improper ventilation, etc, . In India there is no proper standards for Indoor Air Quality Assessment like Ambient Air Quality Assessment. Also the characteristic influencing Indoor Air Quality slightly differs from characteristics of Ambient Air Quality. According to ASHREA standard Indoor Air Quality is characterized with the parameters such as radon, aerosol and bioaerosol, VOC, etc, . Poor Indoor Air Quality can cause Sick Building Syndrome and Building related Illness too. It also influences the human comfort to people inside the building. Indian Buildings both residential and Commercial are constructed without proper ventilation leading to human discomfort and unnoticedindoorairpollutantscancauseserioushealthconcerns.